The relationship between responsible leadership and individual creativity: The mediating role of affective commitment - Simões, L. M.; Duarte, A. P.; Ribeiro, N. (International Conference of Applied Research in Management and Economics (ICARME) - Rethinking management and economics in the (new) 20’s. Book of abstracts, 2022)
This study analyzed how responsible leadership explains individual creativity through the mediation of affective commitment. Responsible leadership confers importance to value creation, change and sustainable development, as well as allowing to experiment with new ideas, thus creating a work environment conducive to creativity (Castro-González et al., 2019). In addition, responsible leadership contributes to employees having positive work experiences, thus promoting the strengthening of the emotional attachment to the organization (Haque et al., 2018; Simões & Duarte, 2021), which has been associated with greater individual creativity (Ribeiro et al., 2020). As a way of testing the proposed research model, a cross-sectional correlational quantitative methodology was used, based on a questionnaire to workers (n=284). Data were analyzed using the PROCESS macro. The results are in agreement with the literature and reveal a positive and significant direct relationship between responsible leadership and individual creativity. They also point to a significant partial mediation by affective commitment, that is, affective commitment significantly mediates the relationship between responsible leadership and employee creativity. We can conclude that affective commitment presents itself as a psychosocial mechanism that helps to explain the relationship between responsible leadership and creativity, which is one of the main contributions of this investigation, since, to our knowledge, there are no studies that integrate these variables in the same model. Therefore, responsible leadership, together with affective commitment, can favor a positive work environment, contributing to the promotion of individual behaviors at work, such as creativity.